The Victorian Time Signal Service - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2020)
A 1945 technical paper from the Telecommunications Journal of Australia is revisited that describes the timing and signalling equipment used at the Melbourne Observatory between 1853 and 1945. The equipment was used to provide the Victorian Time Signal Service for over ninety years.